Clinical implications of Delphian lymph node metastasis in papillary thyroid carcinoma: a single-institution study, systemic review and meta-analysis - Bin Wang; Xing-zhu Wen; Wei Zhang; Ming Qiu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background To evaluate the possible predictive value and clinicopathological characteristics of Delphian lymph node metastasis in papillary thyroid carcinoma. Methods A retrospective analysis of papillary thyroid carcinoma patients with Delphian lymph node metastasis in a single institution and meta-analysis of literature reports were performed. Results In own series, Delphian lymph node metastasis was detected in 19 (9.9%) of 192 papillary thyroid carcinoma patients and was significantly associated with tumor size≥1 cm (P = 0.003), multifocality (P = 0.006) and extrathyroid extension (P < 0.001) in the multivariate analysis. Female was a protective factor for Delphian lymph node metastasis (P = 0.001). Delphian lymph node metastasis was highly predictive of further central lymph node metastasis (positive predictive value = 89.5%, negative predictive value = 67.6%) and moderately predictive of lateral lymph node metastasis (positive predictive value = 26.3%, negative predictive value = 95.4%). In this meta-analysis, there was a strong correlation between Delphian lymph node metastasis and aggressive clinicopathologic characteristics with regards to multifocality (P = 0.0008), bilaterality (P = 0.04), extrathyroid extension (P < 0.00001), lymphovascular invasion (P < 0.00001), further central lymph node metastasis (P < 0.00001) and lateral lymph node metastasis (P < 0.00001). Conclusions This single-institution observational study and meta-analysis identified that Delphian lymph node metastasis was significantly associated with unfavorable clinicopathological characteristics and had a strong predictive power for further disease in the central compartment. Trial registration The clinical study was retrospectively registered to UMIN clinical trials registry (the registry number: UMIN000033835).